วิเคราะห์วิธีการเรียนรู้ในศตวรรษที่ 21 - ศรีนนท์, มนัสวี (วารสาร ศึกษาศาสตร์ มมร, 2017)
บทความนี้มีวัตถุประสงค์ดังนี้ 1) เพื่อศึกษาวิธีการเรียนรู้ก่อนศตวรรษที่ 21 2) เพื่อศึกษาวิธีการเรียนรู้ในศตวรรษที่ 21 3) เพื่อวิเคราะห์วิธีการเรียนรู้ก่อนศตวรรษที่ 21 ผลการศึกษา พบว่า วิธีการเรียนรู้ก่อนศตวรรษที่ 21 นั้นเป็นการให้ความสำคัญกับการพัฒนาภายในและภายนอกตัวมนุษย์เป็นหลัก ส่วนวิธีการเรียนรู้ในศตวรรษที่ 21 นี้เป็นรูปแบบการเรียนรู้ที่อยู่เหนือบุคคล กาลเวลา และสถานที่ จึงจะเป็นการเรียนรู้ที่ยั่งยืนและมั่นคงตลอดไป ABSTRACT The purposes of this article were: 1) to study the learning methods before 21 st Century, 2) to study the learning methods in 21st Century, 3) to analysis the learning methods in 21st Century. The results of the study show that the learning methods before 21 st Century has focused on Internal and external development of human beings. The learning methods in 21st Century is a learning model over people, time and place. It is a long-term learning and stability.